Analysis of the importance of the execution of the Girardot-Honda-Puerto Salgar project, through Public Private Partnerships (2015-2019) (2020)
Public-private partnerships (PPPs) have been consolidated as a technical and financial instrument that facilitates the construction, maintenance and long-term operation of infrastructure at the social and productive level, which guarantees that the State provides the goods and services that correspond to it. Although it is true that the execution of the Fourth Generation Road Concession Program (4G) in Colombia contributes to the country's economic growth, it is important to analyze the impact that the construction of these works has on the surrounding municipalities at the social, economic and environmental levels. They can bring short and long term benefits, such as the generation of employment and the reduction of travel time through the country's roads. This essay is oriented to analyze the importance and benefits brought by the development of the Girardot - Honda - Puerto Salgar road concession, through public-private partnerships in the period from 2015 to 2019, which is a great challenge for the country's progress at an international level, mainly for the infrastructure sector. Taking into account the delays evidenced in the primary roads that Colombia has.